Desenvolvimento de plataforma funcionalizada com CdSe/CdS: associando quantum dots com a eletroquímica - França, Caio César Lima de (2018)
Molecular systems with high sensitivity and specificity have been searched in electrochemistry. Therefore, looking innovation in the development of self assembled layers. The purpose of modifying the surface of an electrode is to increase its physical and chemical stability and interaction with a specific analyte. In this context, host-guest systems are a good alternative for such systems. The use of quantum dots in electrochemistry has increased considerably, due to their optical and electronic properties. The quantum dots are studied extensively in their optical properties, however, its electrical properties are deficient in flowery literature when compared to the volume and quality of literature on the optical properties. In the present study, we sought to develop an electrochemical sensor initially tested with mangiferin (MGN), a natural chemical compound with broad biological aspect, using gold electrode modified with β-cyclodextrin (β-CD) and the quantum dot core structure bark, cadmium selenide/cadmium sulfide (CdSe/dS). This system was characterized opposite the electrochemical properties using the techniques of cyclic voltammetry, differential pulse voltammetry and electrochemical impedance spectroscopy. For characterization front of their optical properties, we used a UV-Vis and fluorescence. Subsequently, it was developed a microfluidic electrochemical system for detecting microdevice mangiferin. We managed to get electrochemical detection by cyclic voltammetry technique in the concentration range of 3 μmolL-1 to 30 μmolL-1 mangiferin smaller range that reported in previous studies, it is noteworthy that we obtained higher peak current; was calculated at constant interaction by the derivative of isotherm Languimur yielding a value of 1.66 X 105 Lmol-1, whereas in previous studies was the constant value of 7.75 X 104 Lmol-1 that is a value 2.15 times greater. Using differential pulse voltammetry was obtained detection of 1 μmolL-1 to 30 μmolL-1. Using UV-Vis there was a shift in the band 368 nm to 380 nm, or a wavelength to which the required energy is lower. In the fluorescence spectroscopy in the presence of CdSe / CdS, an increase of 8 times the intensity of the band compared to the analyzes carried out in the absence of CdSe / CdS. In the microdevice, electrochemical detection was obtained at the concentration of 50 μmolL-1 mangiferin.